Identification of putative substrates for cynomolgus monkey cytochrome P450 2C8 by substrate depletion assays with 22 human P450 substrates and inhibitors. (20th July 2016) - Hosaka, Shinya; Murayama, Norie; Satsukawa, Masahiro; Uehara, Shotaro; Shimizu, Makiko; Iwasaki, Kazuhide; Iwano, Shunsuke; Uno, Yasuhiro; Yamazaki, Hiroshi
Abstract: Cynomolgus monkeys are widely used in drug developmental stages as non‐human primate models. Previous studies used 89 compounds to investigate species differences associated with cytochrome P450 (P450 or CYP) function that reported monkey specific CYP2C76 cleared 19 chemicals, and homologous CYP2C9 and CYP2C19 metabolized 17 and 30 human CYP2C9 and/or CYP2C19 substrates/inhibitors, respectively. In the present study, 22 compounds selected from viewpoints of global drug interaction guidances and guidelines were further evaluated to seek potential substrates for monkey CYP2C8, which is highly homologous to human CYP2C8 (92%). Amodiaquine, montelukast, quercetin and rosiglitazone, known as substrates or competitive inhibitors of human CYP2C8, were metabolically depleted by recombinant monkey CYP2C8 at relatively high rates. Taken together with our reported findings of the slow eliminations of amodiaquine and montelukast by monkey CYP2C9, CYP2C19 and CYP2C76, the present results suggest that these at least four chemicals may be good marker substrates for monkey CYP2C8. Copyright © 2016 John Wiley & Sons, Ltd.